2017
DOI: 10.1002/aur.1818
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐site randomized control trial of the Social ABCs caregiver‐mediated intervention for toddlers with autism spectrum disorder

Abstract: To evaluate the efficacy of the Social ABCs parent-mediated intervention for toddlers with suspected or confirmed autism spectrum disorder (ASD), through a cross-site randomized control trial, sixty-three parent-toddler dyads (toddler age: 16-30 months) were randomized into treatment (Social ABCs) or control (service-as-usual) conditions. Video data were obtained at three key time-points: Baseline; Post-training (PT; week 12); and Follow-Up (week 24). Analyses included 62 dyads. Treatment allocation significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 54 publications
6
107
1
1
Order By: Relevance
“…While many of these showed significant links to outcomes, again these may be nonspecific predictors of which families would benefit from any intervention as opposed to who would benefit from a specific intervention. Of note, were the two studies [Brian et al, 2017;Green et al, 2010] that found no association between parental education and socioeconomic status (SES) and outcome respectively; however as (where available) studies suggest relatively highly educated and higher income participants, the influence of these factors on outcomes warrants further attention. Consistent with Vivanti et al [2014], we concur that family factors, particularly in parent-mediated interventions, require more fine-grained analysis to determine which families a specific intervention would be most effective for and may include variables absent from current investigations including family expectations of treatment, family self-efficacy, parent/therapist alliance, family stress, father positive involvement, and social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of these showed significant links to outcomes, again these may be nonspecific predictors of which families would benefit from any intervention as opposed to who would benefit from a specific intervention. Of note, were the two studies [Brian et al, 2017;Green et al, 2010] that found no association between parental education and socioeconomic status (SES) and outcome respectively; however as (where available) studies suggest relatively highly educated and higher income participants, the influence of these factors on outcomes warrants further attention. Consistent with Vivanti et al [2014], we concur that family factors, particularly in parent-mediated interventions, require more fine-grained analysis to determine which families a specific intervention would be most effective for and may include variables absent from current investigations including family expectations of treatment, family self-efficacy, parent/therapist alliance, family stress, father positive involvement, and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 presents a list of 45 factors pertaining to children and parents examined across studies, which are categorized descriptively as broad (e.g., age, nonverbal ability, ASD severity), fine-grained (e.g., joint attention, imitation), and contextual (e.g., service access during trials, intervention hours) factors. Brian et al [2016] × 10 × 27,28 Brian et al [2017] × 2 × 10 × 27,28 Byford et al [2015] × 7 × 11 × 24 × 26 × 27 × 37 Carter et al [2011] × 28 Casenhiser et al [2013] × 28, 29 Chiang et al [2016] ✓ 12 × 13 × 27,28 Cook et al [2017] × 1 × 23 ✓ 30 × 31 Green et al [2010] × 7 × 11 × 24 × 26 × 27 Gulsrud et al [2016] × 33 Hardan et al [2015] ✓ 3 ✓ 14 ✓ 15 × 27,28 × 34 Harrop et al [2017] × 33 Ingersoll et al [2016] × 37 Kasari et al [2015] × 33 Kasari et al [2014] ✓ 11 × 28 Kasari et al [2010] × 28 Kuravackel et al [2017] × Note. ✓ = inclusion; × = exclusion.…”
Section: Potential Mediating and Moderating Factorsmentioning
confidence: 99%
“…Evidence for generalisation is modest; independent global impression of social communication from same tapes alongside parent interview reported improvements as did parent‐reported communication on Vineland, but there was no effect in parent‐reported language use, standard language measures or parent‐rated autism behaviours. A subsequent similar intervention model combining PRT and ABA reported effects on dyadic joint engagement and shared enjoyment but also no generalised effect (Brian, Smith, Zwaigenbaum, & Bryson, ).…”
Section: Targets and Mechanisms In Psychosocial Autism Interventionmentioning
confidence: 98%
“…Improved prompted 'child utterances' with parent (Hardan et al, 2015) Reciprocal dyadic behaviours Dyadic joint engagement, joint attention, joint play Joint engagement (JE) measure JE improved with JASPER (Kasari 2008, Kaale et al, 2014 Increased joint engagement and play (Shire et al, 2017) No gains in shared affect (Landa et al, 2011). Short term improved emotional engagement but no follow up effect (Brian et al, 2017).…”
Section: Parent Intrusiveness/ Directivenessmentioning
confidence: 99%
“…For children diagnosed with ASD, increased levels of positive affect and spontaneous speech immediately followed intervention that targeted joint attention [Whalen et al, ]. The PRT‐based, parent‐implemented Social ABCs intervention for toddlers at risk of ASD targets reciprocal positive affect between children and their parents to enhance early communication [Brian, Smith, Zwaigenbaum, & Bryson, ].…”
mentioning
confidence: 99%